Integrated Digital Human Capital Model: From VRIN (RBV) Resources to Transformation Capabilities (DCT) and Company Performance. - Isnawati, Isnawati; Hendayana, Yayan (Dinasti Publisher, 2025)
The hyper-dynamic business environment in technology companies requires companies to not only have a competitive advantage, but also the ability to consistently sustain that advantage. This literature review article aims to formulate a new conceptual framework that explains how Strategic Human Resource Management (SHRM) transforms internal resources into superior performance. This model is based on the Resource-Based View (RBV), which identifies Digital Human Capital (DHC) as the primary VRIN (Valuable, Rare, Inimitable, Non-substitutable) resource. This integration is expanded with Dynamic Capabilities Theory (DCT), where SHRM is hypothesized as the main mechanism for sensing, seizing, and transforming HCD to align with market demands. At the micro level, Social Cognitive Theory (SCT) provides a behavioral foundation that explains employee self-efficacy and collective learning as drivers of these dynamic capabilities. Through extensive literature analysis, it was found that the relationship between resource ownership (RBV) and performance is facilitated by dynamic processes (DCT) that are fundamentally driven by SHRM. This article also highlights the relevance of Resource Dependency Theory (RDT) in the context of talent acquisition, complementing the internal perspective. The main contribution is the proposal of a comprehensive model that bridges the macro strategic view with the micro behavioral foundation in the context of digital HR.